Anxiety and Reinforcement Sensitivity in Adolescents - Pavićević, Miljana S.; Minić, Jelena Lj. (Collection of Papers of the Faculty of Philosophy in Priština, 2019)
Theoretical background of this paper is Gray’s reformulated reinforcement sensitivity theory and Spielberger’s model of anxiety as a personality trait. It is a well-founded and a well-known conception which is also highly controversial. The paper is a part of a larger research on mental health of the Kosovo and Metohija youth. The aim of this research is to examine predictive power of trait anxiety in predicting reinforcement sensitivity (through the systems: FFF; BIS, and BAS). The sample of the research encompassed adolescents (N=138). Results gained point that the anxiety trait is more rendered in those adolescents with more inhibition and avoidance exhibited, as well as BIS. Also, trait anxiety is more rendered in the adolescents with a lower BAS. Statistically significant relationship between trait anxiety and the fight is not found. Persons with more exhibited anxiety show inability to react to endangering situations, they step back to avoid new situations, and perceive their environment as a source of potential danger.
Keywords: anxiety; reinforcement sensitivity; adolescents